Markowitz Model in The Analysis of Optimal Portfolio Establishment on Jakarta Islamic Index (JII) in Indonesian Stock Exchange - Ramli, Anwar; Anwar; Anwar, Indah Lestari (Archives of Business Research, 2020)
This study aims to know the optimal portfolio establishment using Markowitz model on Jakarta Islamic Index (JII) stocks in the period of December 2013-May 2019. The population of this study consisted of the company stocks on Jakarta Islamic Index (JII) in the period of December 2013-May 2019, and there were 59 stocks. While the study sample consisted of 14 company stocks and selected based on purposive sampling method. Data collection used in this study using documentation. Data analysis used in this study using the stages of Markowitz model and started collecting the close price until an optimal portfolio establishment. The result of this study showed that there were 8 company stocks included in the optimal portfolio. Namely AKRA (5,01%), ICBP (9,92%), INDF (3,75%), SMGR (8,61%), TLKM (29,01%), UNTR (20,30%), UNVR (20,88%), WIKA (2,53%). The expected return of the portfolio of 0,84%. Therefore, portfolio risk of 3,16%and smaller than the risk of individual stocks in the research sample.